2010
DOI: 10.1007/s12079-010-0103-1
|View full text |Cite
|
Sign up to set email alerts
|

Steroid signaling activation and intracellular localization of sex steroid receptors

Abstract: In addition to stimulating gene transcription, sex steroids trigger rapid, non-genomic responses in the extra-nuclear compartment of target cells. These events take place within seconds or minutes after hormone administration and do not require transcriptional activity of sex steroid receptors. Depending on cell systems, activation of extra-nuclear signaling pathways by sex steroids fosters cell cycle progression, prevents apoptosis, leads to epigenetic modifications and increases cell migration through cytosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…F blocked T effects in U87 and U251 cells, but this blockade was only partial in D54 cells, revealing the participation of other mechanisms that could regulate the activity of T, such as the membrane androgens receptor, whose action by the non-classical mechanism has recently been described in prostate cancer and Sertolli cells (32). It has been described that non-genomic androgen actions regulate proliferative/migratory signaling in stromal cells (33), steroid signaling activation and intracellular localization of sex steroid receptors (34).…”
Section: Discussionmentioning
confidence: 99%
“…F blocked T effects in U87 and U251 cells, but this blockade was only partial in D54 cells, revealing the participation of other mechanisms that could regulate the activity of T, such as the membrane androgens receptor, whose action by the non-classical mechanism has recently been described in prostate cancer and Sertolli cells (32). It has been described that non-genomic androgen actions regulate proliferative/migratory signaling in stromal cells (33), steroid signaling activation and intracellular localization of sex steroid receptors (34).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of NLS with importins and microtubule‐associated molecular motor proteins appears to mediate NHR transport to the nucleus . It also was reported that ERα contains a leucine‐rich nuclear export sequence (NES) in the LBD . The NES, through binding to an exportin, was suggested to modulate the nucleocytoplasmic shuttling of ERα …”
Section: β‐Estradiol–estrogen Receptor Signalingmentioning
confidence: 99%
“…However, the functions of steroid hormones in esophageal cancer are often ignored, although there are significant gender differences in esophageal cancer patients. Steroids can affect cell behaviors through non-genomic and genomic actions ( 11 ). Thus, studying the functions and mechanisms of steroids and steroid antagonists holds great promise for esophageal cancer treatment and prevention.…”
Section: Introductionmentioning
confidence: 99%